2015
DOI: 10.1007/s00508-015-0782-y
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of patients to long-term medication: a cross-sectional study of antihypertensive regimens in Austria

Abstract: The objective of this study was to evaluate adherence and causes for non-adherence to antihypertensive therapy in Austrian patients. A special focus was laid on social parameters and behavioural theories. Methods:Patients were invited via advertisements in community pharmacies in Austria to complete an online survey. Inclusion criteria were an age of 18 years or older, a diagnosis of arterial hypertension and a current prescription of antihypertensive medication. Adherence was measured by the 4-item Morisky sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…The median sample size for all surveyed studies was 885 participants (range 109‐7425), with a total of 27 441 participants included in this review. Eleven studies were based in North America, 7 in Asia, 5 in South America, 4 in Europe, 2 in Africa, and 3 were conducted in multiple countries . The most common condition studied was Hypertension (n = 27).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median sample size for all surveyed studies was 885 participants (range 109‐7425), with a total of 27 441 participants included in this review. Eleven studies were based in North America, 7 in Asia, 5 in South America, 4 in Europe, 2 in Africa, and 3 were conducted in multiple countries . The most common condition studied was Hypertension (n = 27).…”
Section: Resultsmentioning
confidence: 99%
“…The studies reported the outcomes in 4 ways: overall non‐adherence to medication (n = 10), non‐adherence to individual classes of medications (n = 11), overall adherence to medication (n = 8) and adherence to individual classes of medications (n = 2) . Prevalence of overall non‐adherence to medication ranged from 8.2 to 74.9%; whereas non‐adherence to individual classes of medication ranged from 4.0 to 75.8%; overall adherence to medication ranged from 21.2 to 78%; and adherence to individual classes of medication ranged from 15.0 to 77.4%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…возрастным. Молодые пациенты с артериальной гипертензией в этом отношении наименее обследованы, хотя в последние годы получены данные зарубежных ученых [10,11]. Следует указать, однако, на то, что в условиях различных экономических систем, систем здравоохранения вклад факторов, влияющих на приверженность терапии, существенно различается [12].…”
Section: Discussionunclassified